DSTS and Modeling Tools Report - Ministry of Water Resources and Meteorology, Cambodia; Tonle Sap Authority; Supreme National Economic Council, Cambodia; Hatfield Consultants; Culture and Environment Preservation Association (2014)
Decision Support Tools (DSTs) have been developed by various organisations (government agencies, international organizations, NGOs, universities, consultancy companies and think tanks) to facilitate decision making around a number of issues, including water governance and management. There are arange of DSTs, distinguished by their function, quality of services (accuracy and precision), ease of use, time of application (project planning, implementation, monitoring, etc.), data requirements, data generated and other factors. The main objective of this analysis is to assess currently available and relevant decision support tools (DSTs), and to highlight the method of selecting most appropriate tool.